AB0880 The objective automated measurement of fluorescence-signal intensities in fluorescence-optical imaging technique discriminates between disease activity and its response in antitnf treated psoriatic arthritis patients – an interims analysis of the xplore-study. (12th June 2018) - Köhm, M.; Ohrndorf, S.; Rossmanith, T.; Foldenauer, A.; Henkemeier, U.; Schmittat, G.; Berger, J.; Burkhardt, H.; Behrens, F.; ,
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory disorder combining joint and musculoskeletal inflammation. AntiTNF-therapy is induced after failure of NSAID and DMARD treatment. Up to 30%–40% of the patients are primary not responding adequately to the induced biological therapy. In daily practice response is calculated by improvement of disease activity measured by clinical examination and calculated using composite indices. Feasible and robust biomarkers for prediction of response are missing. Methods: Fluorescence optical imaging (FOI) is used as method for detection of changes in microvascularisation of the hands as potential marker for inflammation. ICG is injected as fluorescence agent, that is than stimulated by light and recorded by a specific camera system. An automated computer-based reading of the disease activity (DACT) is used as an objective method to display overall fluorescence-signals and their intensities. In a prospective multicentre study, the value of FOI in measurement of disease activity and its predictive value to discriminate responders in newly treated PsA patients is currently investigated in the XPLORE-study. This interim analysis investigates the value of baseline (BL) DACT to discriminate between responders (at least low disease activity (LDA) with DAS28 ≤3.2) and non-responders compared to standard clinical disease measurements (SJC, TJC, DAS28) over the 52 weeks observational period. Results: Data from 23 patients were analysed during the 52 weeks observational period. Mean age was 54.7 years, 60% of the patients were female. Mean DAS28 at baseline was 4.26, mean BSA 9%, whereas mean values for SJC were 5.9 and TJC 11.4 using 66/68 joint count. All patients were negative for ACPA and rheumatoid factor. ROC analysis revealed that a DACT cut-off of 4.55 at baseline, indicating moderate expression of fluorescence intensities in context of disease activity, shows a predictive quality to LDA achievement at W52 with 80% specificity, 78% sensitivity and likelihood ratios of 3.89 (LQ+) and 0.28 (LQ-). The corresponding AUC value is 0.717 (95%CI=[0.393, 1]; p=0.146). Compared to clinical disease measurements such as baseline DAS28, TJC or SJC, the DACT at BL is more discriminative to identify patients who attain LDA at W52. Conclusions: This interim analysis of the XPLORE study shows promising data for the use of FOI as possible imaging biomarker for disease activity measure and prediction of response in PsA-patients newly treated with antiTNF-therapy: Baseline values evaluated using the automated computer-based reading of the fluorescence intensities with a cut-off of 4.55 are predictive for later achievement of DAS28 low-disease activity or remission within the treatment course. Data will be verified in a larger cohort of the XPLORE study. Disclosure of Interest: M. Köhm Grant/research support from: Pfizer Germany, S. Ohrndorf: None declared, T. Rossmanith: None declared, A. Foldenauer: None declared, U. Henkemeier: None declared, G. Schmittat: None declared, J. Berger Employee of: Xiralit GmbH, H. Burkhardt Grant/research support from: Pfizer Germany, F. Behrens Grant/research support from: Pfizer Germany